Clinical impact of hypomagnesemia induced by necitumumab plus cisplatin and gemcitabine treatment in patients with advanced lung squamous cell carcinoma: a subanalysis of the NINJA study - Shigeru Tanzawa; Hiroshige Yoshioka; Toshihiro Misumi; Eisaku Miyauchi; Kiichiro Ninomiya; Yasunori Murata; Masafumi Takeshita; Fumihiko Kinoshita; Takatoshi Fujishita; Shunichi Sugawara; Yosuke Kawashima; Kazuki Hashimoto; et al. (Therapeutic Advances in Medical Oncology)
Background: The clinical impact of hypomagnesemia induced by necitumumab plus gemcitabine and cisplatin (GCN) as a second-line or later therapy is unclear. Objective: We aimed to evaluate the clinical characteristics and survival impact of hypomagnesemia induced by this therapy. Design: This was a sub-analysis of the retrospective multicenter NINJA study. Methods: Among the 93 patients enrolled in the NINJA study, this subanalysis included 75 patients with baseline serum magnesium concentrations. Results: The incidence of grade ⩾2 hypomagnesemia was 18.0% in the patients with normal baseline serum magnesium concentrations and 42.8% in those with low concentrations ( p  = 0.073). The discontinuation rates of GCN treatment owing to hypomagnesemia in each group were 0% and 7.1%, respectively ( p  = 0.187). The number of necitumumab doses and severity of hypomagnesemia were positively correlated ( r  = 0.389, p  < 0.001). Patients who developed hypomagnesemia in fewer than 21 days after the first dose of GCN ( n  = 12) had significantly poorer progression-free survival (PFS) than those without the condition ( n  = 63; median: 4.1 vs 4.4 months, p  = 0.048). A similar trend was observed for OS (median: 9.7 vs 15.7 months, p  = 0.062). These results were maintained after multivariate analyses (PFS: hazard ratio (HR) 2.46, p  = 0.014; OS: HR 2.78, p  = 0.021). Conclusion: GCN as a second-line or later therapy may be tolerable regardless of the patient’s baseline serum magnesium concentration. On the other hand, early serum magnesium reduction with this therapy is associated with a poor prognosis. However, caution should be needed because our results lacked sufficient information for confounding variables other than those analyzed here that may influence the correlation between hypomagnesemia and survival.